3. KNOWLEDGE AND PRACTICE OF COMPLIANCE WITH TREATMENT OF PATIENTS HYPERTENSION AT MEDICINE AND PHARMACY UNIVERSITY HOSPITAL, HANOI NATIONAL UNIVERSITY IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current status of knowledge and practice of treatment adherence among patients with hypertension. Methods: Cross-sectional survey, quantitative research. Results and conclusion:- Level of general knowledge of patients with hypertension: 56.9% of patients have satisfactory knowledge about the treatment of hypertension, of which only 50.0% have satisfactory knowledge about hypertension indicators, 52.9% correctly and fully list the risk factors leading to hypertension and only 35.1% correctly understood the signs of hypertension requiring immediate hospitalization. 95.1% of patients answered correctly that the principle of using medication to treat hypertension is to take it continuously and long-term as prescribed by the doctor. 88.6% of patients answered correctly that the principle of treating hypertension is using medication combined with lifestyle changes and 61.7% had correct knowledge about lifestyle. - Level of patient compliance with hypertension treatment 60.6% of patients measure their blood pressure daily, 57.4% of patients follow a low-salt diet, 32.9% exercise daily and especially only 24.3% perform well measures to reduce blood pressure. paroxysmal hypertension room. 76.9% of patients did not forget to take their medication, 68.9% did not arbitrarily cut down on medication, 75.4% did not stop taking medication when they felt their symptoms were under control, and 46.9% of patients forgot to bring their medication when they went. play or travel. Recommendation: Strengthen proactive health care communication and education for hypertensive patients on knowledge and practice of treatment compliance.
Keywords: Treatment adherence, knowledge, practice, patients, hypertension.